Perspectives surrounding fertility preservation and posthumous reproduction for adolescent and young adults with terminal cancer: Survey of allied health professionals. (13th October 2022) - Barrett, Francesca; Sutter, Megan E.; Campo‐Engelstein, Lisa; Sampson, Amani; Caplan, Arthur; Lawrence, Morgan; Vadaparampil, Susan T.; Quinn, Gwendolyn P.
Abstract: Background: While all reproductive‐aged individuals with cancer should be offered fertility preservation (FP) counseling, there is little guidance over offers to adolescent and young adults (AYA) with terminal diagnoses, especially when considering posthumous assisted reproduction (PAR). The Enriching Communication skills for Health professionals in Oncofertility (ECHO/ENRICH) trains Allied Health Professionals (AHPs) to improve communication with AYAs with cancer. Little is known about AHPs' role in assisting in FP and PAR decisions. Methods: This is a cross‐sectional survey of ECHO/ENRICH trainees' attitudes and experience with FP and PAR in AYA with terminal cancer. Results: The response rate was 61% (365/601). While 69% felt comfortable discussing FP with terminal AYA after ECHO/ENRICH training, 85% desired further education. The majority (88%) agreed FP should be an option for AYA with cancer, though some agreed offering FP provided false hope (16%) or was a waste of resources (7%). Most shared that avoidance of FP discussions was common practice, especially in the medically fragile, late‐stage disease, or among minors. Many attributed lack of conversations to oncology team goals. Only 9% had prior experience with PAR. Many were conflicted about how PAR reproductive material should be gifted and who should be permitted to use PAR. Several raised moral concerns for PAR, or discomfort advising family. Many voiced desire for additional PAR‐specific education. Conclusion: ECHO/ENRICH trainees had varied levels of exposure to FP in terminal AYA and limited experiences with PAR. Many expressed uncertainties with PAR, which may be alleviated with further training and transparent institutional policies. Abstract : Allied Health Professionals who were ECHO/ENRICH trainees had varied levels of exposure to fertility preservation in terminally ill adolescent and young adults with cancer and limited experiences with posthumous assisted reproduction. Many expressed uncertainties with posthumous assisted reproduction, which may be alleviated with further training and transparent institutional policies.